Anthropometric Characteristics, Training Intensity Distribution, Physiological Profile and Performance of an Elite Trail Runner: A Longitudinal Case Study; [Características Antropométricas, Distribución de la Intensidad del Entrenamiento, Perfil Fisiológico y Rendimiento de Un Corredor de Montaña de Élite: Un Estudio de Caso Longitudinal] - Soto-Lagos, R (Universidad de la Frontera, 2024)
Trail running (TR), an extreme endurance sport, presents unique challenges due to the variety of terrain and distances, where physiological capacity and body composition have been considered better predictors of performance. This longitudinal case study examines the impact of training intensity distribution (TID) on an elite trail runner s physiological profile and performance over four years. Two TID models were implemented: polarized (POL) and pyramidal (PYR). Physiological assessments included maximal oxygen consumption (VO2max), lactate thresholds (LT1 and LT2), and anthropometric characteristics. The training was classified according to the 3-zone intensity model (zone 1: below the first lactate threshold; zone 2: between the first and second lactate threshold; zone 3: above the second lactate threshold). During the four years, the average TID distribution was 75 % zone 1, 18 % zone 2, and 7 % zone 3. Physiological capacity increased by 7.14 % (14 to 15 km/h) for velocity at LT1 (vLT1) and 8.13 % (16 to 17.3 km/h) for velocity at LT2 (vLT2). The most significant increases were observed during the second year when the percentage of training time in zone 1 was lower (65 %) and in zone 2 greater (30 %) than those reported in other years. Consequently, vLT1 and vLT2 increased by 3.5 % (from 14.1 to 14.6 km/h) and 3.6 % (from 16.5 to 17.1 km/h), respectively. In conclusion, this case study revealed that emphasizing training in zone 2 (moderate intensity) and increasing the training load significantly improved performance at lactate thresholds. Despite modifying body composition, no influence on improving endurance performance was observed. These findings underscore the importance of TID in elite trail runners and highlight the potential to optimize physiological adaptations and performance outcomes. © 2024, Universidad de la Frontera. All rights reserved.
Keywords: Body Composition Assessments; Exercise Physiology; Sport Performance; Trail Running; Training Intensity Distribution